Pengaruh Kompetensi dan Disiplin kerja Terhadap Kinerja Pegawai PT Nesinak Industries - Akbar Finardi; Eman Sulaeman (Peneliti.net, 2023)
In the era of modern organizations that are constantly developing, the role of employees or employees is very important in maintaining the continuity and success of the company. This research was conducted to find out how much influence competence and work discipline have on Employee Performance at PT Nesinak Industries. This research is in the form of descriptive and verification research with a quantitative approach. The sampling technique in this study used stratified random sampling with a sample of 234 respondents, namely employees of PT Nesinak Industries. In this study, the data validity test and classical assumption test were carried out. The data analysis technique used is the Scale Range Analysis and Path Analysis techniques with the help of Microsoft Excel and SPSS. Based on the results of this study indicate that the variables of competence and work discipline have a positive and significant effect on employee performance.